Genes From Microorganisms Used as Biomarkers to Detect Soil Health - Rubio-Valdez, Jonathan Noé; Chávez-Simental, Jorge Armando; Ortiz-Sánchez, Ixchel Abby; Alba-Fierro, Carlos Antonio; Cabral-Miramontes, Juan Pablo (REVISTA TERRA LATINOAMERICANA, 2025)
Soil health is essential for ecosystem stability, biodiversity, and food security. Soil degradation and contamination adversely af fect soil fertility; therefore, continuous monitoring of physicochemical and biological indicators is required to support sustainable agricultural systems. Biosensors enable the detection of analytes in soil and water, providing rapid alerts and complementing conventional analytical methods. These biosensors, which may include tissues, microbial cultures, enzymes, and antibodies, are widely applied in environmental monitoring, food safety, and medical fields for the detection of a broad range of analytes. In this context, the use of reporter genes endogenously present in organisms is recommended, as they allow the detection of compounds under specific conditions and are extensively used due to their precision and accurate quantification of contaminant concentrations. This review article compiles updated global information with the objective of synthesizing the most relevant factors af fecting soil functionality and limiting its productive potential; additionally, it aims to provide a comprehensive overview of the importance of, and alternatives developed in, various studies for assessing soil health, thereby supporting timely decision-making for its immediate management.